Giant electric field tunable magnetic properties in a Co50Fe50/lead magnesium niobate–lead titanate multiferroic heterostructure. (3rd July 2015) - Yang, Wei-Gang; Morley, Nicola A; Sharp, Joanne; Rainforth, W Mark
Abstract: Co50 Fe50 /(0 1 1)-oriented lead magnesium niobate–lead titanate (PMN–PT) multiferroic (MF) heterostructures were fabricated by RF sputtering magnetic films onto PMN–PT substrates. The effect of magnetic layer thickness (30 nm to 100 nm) on the magnetoelectric (ME) coupling in the heterostructures was studied independently, due to the almost constant magnetostriction constant ( λ = 40 ± 5 ppm) and similar as-grown magnetic anisotropies for all studied magnetic layer thicknesses. A record high remanence ratio ( M r / M s ) tunability of 95% has been demonstrated in the 65 nm Co50 Fe50 /PMN–PT heterostructure, corresponding to a large ME constant ( α ) of 2.5 × 10 −6 s m −1, when an external electric field ( E -field) of 9 kV cm −1 was applied. Such an MF heterostructure provides considerable opportunities for E -field-controlled multifunctional devices.